2013
DOI: 10.1021/jm4007752
|View full text |Cite
|
Sign up to set email alerts
|

A Medicinal Chemistry Perspective for Targeting Histone H3 Lysine-79 Methyltransferase DOT1L

Abstract: Histone H3 lysine79 (H3K79) methyltransferase DOT1L plays an important role in the activation and maintenance of gene transcription. It is essential for embryonic development as well as normal functions of the hematopoietic system, heart and kidney in adults. DOT1L has been found to be a drug target for acute leukemia with mixed lineage leukemia (MLL) gene translocations. The rearranged onco-MLL can recruit DOT1L, causing aberrant H3K79 methylation, overexpression of leukemia relevant genes, and eventually leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 64 publications
0
73
0
1
Order By: Relevance
“…DOT1L has also been found to be associated with mixed lineage leukemia (MLL) fusion proteins, resulting in aberrant methylation patterns of H3K79 and dysregulation of MLL targeted genes (Okada et al 2005). Clinical trials are currently underway using DOT1L-targeting drugs in MLL (Anglin and Song 2013). Methylation of H4K20 is regulated by the PR-SET7 methyltransferase in a cell cycle-dependent manner (Nishioka et al 2002), and these modifications have been shown to play a role in DNA damage responses by attracting TP53BP1 (Beck et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…DOT1L has also been found to be associated with mixed lineage leukemia (MLL) fusion proteins, resulting in aberrant methylation patterns of H3K79 and dysregulation of MLL targeted genes (Okada et al 2005). Clinical trials are currently underway using DOT1L-targeting drugs in MLL (Anglin and Song 2013). Methylation of H4K20 is regulated by the PR-SET7 methyltransferase in a cell cycle-dependent manner (Nishioka et al 2002), and these modifications have been shown to play a role in DNA damage responses by attracting TP53BP1 (Beck et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…3A–C) [150]. The first three segments are consensus sequence motifs also found on other SAM-dependent methyltransferases, whereas the last two segments are unique to DOT1L [151]. Additionally, a flexible and positively charged region between amino acid residues 390 and 407 is critical for nucleosome/DNA binding and methyltransferase activity [150].…”
Section: Structural and Chemical Basis Of Dot1l-mediated H3k79 Methylmentioning
confidence: 99%
“…However, SAH inhibits binding of the cofactor SAM to most of the SAM-dependent methyltransferases [151]. In 2011, the first-in-class aminonucleoside-based DOT1L specific inhibitor EPZ004777 that selectively suppresses leukemia cells with MLL1 translocations was identified (Fig.…”
Section: Development Of Small Molecular Dot1l Inhibitorsmentioning
confidence: 99%
“…They have developed a small molecule inhibitor EPZ-5676, which is currently the first and only inhibitor that has entered clinical trials for the treatment of MLL-rearranged leukemia [27]. EPZ-5676, together with hundreds of other inhibitors developed by Epizyme, was identified by the classic ligandbased design and the following painstaking work of optimization [28][29][30]. As a result, all inhibitors derived from the S-adenosyl-L-homocysteine (SAH) contain the adenosine-like moiety which can be easily targeted and decomposed by endogenous enzymes.…”
Section: Introductionmentioning
confidence: 99%